Interleukin-1 Enhances the ATP-Evoked Release of Arachidonic Acid from Mouse Astrocytes - Stella, Nephi (J Neurosci, 1997)
During neuropathological states associated with inflammation, the levels of cytokines such as interleukin-1β (IL-1β) are increased. Several studies have suggested that the neuronal damage observed in pathogenesis implicating IL-1β are caused by an alteration in the neurochemical interactions between neurons and astrocytes. We report here that treating striatal astrocytes in primary culture with IL-1β for 22–24 hr enhances the ATP-evoked release of arachidonic acid (AA) with no effect on the ATP-induced accumulation of inositol phosphates. The molecular mechanism responsible for this effect involves the expression of P(2Y2) receptors (a subtype of purinoceptor activated by ATP) and cytosolic phospholipase A2 (cPLA(2), an enzyme that mediates AA release). Indeed, P(2Y2) antisense oligonucleotides reduce the ATP-evoked release of AA only from IL-1β-treated astrocytes. Further, both the amount of cPLA2 (as assessed by Western blotting) and the release of AA resulting from direct activation of cPLA(2) increased fourfold in cells treated with IL-1β. We also report evidence indicating that the coupling of newly expressed P(2Y2) receptors to cPLA(2) is dependent on PKC activity. These results suggest that during inflammatory conditions, IL-1β reveals a functional P(2Y2) signaling pathway in astrocytes that results in a dramatic increase in the levels of free AA. This pathway may thus contribute to the neuronal loss associated with cerebral ischemia or traumatic brain injury.